2008
DOI: 10.1007/s00787-008-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DSM-IV disorders in Chinese adolescents and the effects of an impairment criterion

Abstract: While the findings reported here are broadly compatible with those of other studies, there may be cross-cultural differences in rates of some individual disorders, e.g., GAD, depressive disorders, ODD, CD, and substance use disorders, as well as in gender difference regarding rates of ODD and CD. However, exact comparison between studies is confounded by methodological differences in sample characteristics, measures, and case definition. Standardization of methodology in epidemiological surveys should allow mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 39 publications
5
71
5
Order By: Relevance
“…On the other hand, our result is higher than that found in Denmark (5.7%) (24), Italy (5.8%) (23) and China (6.9%) (11). Again the have a greater effect on females.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, our result is higher than that found in Denmark (5.7%) (24), Italy (5.8%) (23) and China (6.9%) (11). Again the have a greater effect on females.…”
Section: Discussioncontrasting
confidence: 87%
“…In China, however, adolescents and their parents completed the youth and parent versions of the Diagnostic Interview Schedule for Children-Version (DISC-IV). Furthermore, the sample represented adolescents in 7th to 9th grades (11). Other studies in the Arab world, such as Gaza and Saudi Arabia, showed that the prevalence of anxiety disorders was much higher than our finding (15,30,31).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Epidemiological findings suggested that Hong Kong Chinese children face the same kind of developmental and mental health challenges as those faced by children in the West (Leung et al 2008). Eisenberg and colleagues found that Chinese and U.S. children have similar patterns of effortful control and emotionality (Zhou et al 2004;Eisenberg et al 2007).…”
Section: The Sel Situation In Hong Kongmentioning
confidence: 99%
“…A local study of the prevalence of DSM-IV disorders in Chinese adolescents pointed out that figures would be overestimated if the impairment criteria were not taken into account. 35 Although MABC used alone would probably overdiagnose DCD by not considering the impairment factors, it is worth noting that 17.9% of our study candidates had definite motor problems. This is actually below the 5th percentile of the general population.…”
Section: Discussionmentioning
confidence: 83%